CURRENT RATIO DAN RETURN ON ASSETS TERHADAP STRUKTUR MODAL DI BURSA EFEK INDONESIA - Hidayat , Rahmat Hidayat; Putri, Vera Ika; Harahap, Dita Sayidina (Catholic University Musi Charitas, 2020)
This research aims to determine the effect of current ratio on capital structure (DAR) and return on assets on capital structure (DAR) listed on the Indonesia Stock Exchange. Population and samples used in this study were 8 advertising, media, and printing companies listed on the Indonesia Stock Exchange in the 2011-2015 period. The sample used was purposive sampling. The data analysis technique used is multiple linear regression. The results showed that partially the influence of the current ratio on capital structure (DAR) with a sig value of 0.076, there was an effect of return on assets on capital structure (DAR) with a sig value of 0.025. The simultaneous results show that the current ratio and return on assets influence the capital structure with a sig value of 0.011. The amount of the coefficient of determination (R-Square) is 0.956. This shows that 95.6% of the dependent variable, namely capital structure (DAR), can be explained by the independent variables, namely Current Ratio and Return On Assets.